Structural applications of bamboo - Sk. Abdus Salam; Abang Ali, Abang Abdullah; Yap, Chee Lin (Institusi Jurutera Malaysia, 1990)
This experimental study to determine the structural application of Malaysian bamboo is divided into three main parts, namely a study on the physical and mechanical properties of three selected species of bamboo, testing of four types of bamboo connectors in king-post trusses and two mono-pitch trusses for buildinqs, Of the four bamboo connectors tested it was found that the bolted plywood bamboo connector showed better strength results, The other types of bamboo connectors tested suffered considerable slip at the joints. The monopitch bamboo truss is of sufficient strength to be utilized for house construction. A spacing of up to two metres could be used it the trusses are to carry a corrugated asbestos roof over a span of 4.5 metres.